2021
DOI: 10.1080/15283488.2021.1947819
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Exploration: Identity Exploration in Real-Time Interactions among Peers

Abstract: In this short-term longitudinal study, we examine specific examples of identity exploration in real-time interactions among peers. The participants included 12 first-year students majoring in literature, social sciences, and humanities at a national university in Japan (M age = 18.2; SD = 0.39; 83.3% female). They were divided into four triads that participated in weekly 20-minute discussions for nine successive weeks around three identity domains: learning, romantic relationships, and career. Transcripts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Alternative, more concrete ways to grasp the real‐time experiences that contribute to identity formation are needed, particularly as many identity processes might be unconscious (Schachter, 2018 ). A recent qualitative study examined the concrete micro‐level exploration behaviors adolescents engage in during real‐time interactions with their peers and showed three overarching interaction patterns that advanced exploration: creating a safe environment for exploration, clarifying and elaborating an idea, and a process in which finding a keyword and repeating it helped adolescents explore an aspect of identity and find tentative, emerging commitments (Sugimura, Gmelin, van der Gaag, & Kunnen, 2021 ). Also, among students conducting a clinical internship, real‐time fulfillment versus frustration of the need for competence, relatedness, and autonomy was related to stronger and weaker commitments, respectively (Kunnen, 2021 ).…”
Section: Intraindividual Processes and Interindividual Differencesmentioning
confidence: 99%
“…Alternative, more concrete ways to grasp the real‐time experiences that contribute to identity formation are needed, particularly as many identity processes might be unconscious (Schachter, 2018 ). A recent qualitative study examined the concrete micro‐level exploration behaviors adolescents engage in during real‐time interactions with their peers and showed three overarching interaction patterns that advanced exploration: creating a safe environment for exploration, clarifying and elaborating an idea, and a process in which finding a keyword and repeating it helped adolescents explore an aspect of identity and find tentative, emerging commitments (Sugimura, Gmelin, van der Gaag, & Kunnen, 2021 ). Also, among students conducting a clinical internship, real‐time fulfillment versus frustration of the need for competence, relatedness, and autonomy was related to stronger and weaker commitments, respectively (Kunnen, 2021 ).…”
Section: Intraindividual Processes and Interindividual Differencesmentioning
confidence: 99%
“…Indeed, a prior study showed that a group-based intervention encouraging young adults' self-understanding and identity exploration through discussion with group members reduced their identity distress ( 57 ). It is effective to apply such exercises to group counseling in the student counseling room or university classes on career guidance ( 58 ). Furthermore, for young adults who hesitate to attend a face-to-face discussion, an interactive text-based intervention may be effective ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, in traditional societies, a person's identity is formed directly from the present culture and is followed by norms and values that are common and specific to the type of social organization (Kurtz, 2022;Rawls & Turowetz, 2021).According to the sociologist, the term "identity" refers to two interconnected aspects of a person's place in society: knowledge of the system in which they operate awareness of the problem and norm of self-determination and their place in the normative space. In this case, identity is not a state but a structural characteristic of a person (Sugimura, Gmelin, van der Gaag, & Kunnen, 2022). Social identity is addressed within the framework of symbolic interactionism.…”
Section: Definition Of the Term Identitymentioning
confidence: 99%